Analisis Isi Eksploitasi Dan Penistaan Agama Dalam Poster Film Kiblat: Content Analysis Of Exploitation And Blasphemy In Kiblat Movie Posters - Arfian Suryasuciramdhan; Della Meira; Elok Kemala Motik; Deswita Fitrianti (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2024)
Film is a part of mass media communication is audio-visual and aims to convey a certain social or moral message to the audience. The method used in this study is a descriptive qualitative method using literature. The Film” KIBLAT